A novel preoperative risk score to guide patient selection for resection of soft tissue sarcoma lung metastases: An analysis from the United States Sarcoma Collaborative. Issue 8 (10th August 2021) - Lee, Rachel M.; Ethun, Cecilia G.; Gamboa, Adriana C.; Turgeon, Michael K.; Tran, Thuy; Poultsides, George; Grignol, Valerie; Bedi, Meena; Mogal, Harveshp; Clarke, Callisia N.; Tseng, Jennifer; Roggin, Kevin K.; et al.
Abstract: Background: Surgical resection for sarcoma lung metastases has been associated with improved overall survival (OS). Methods: Patients who underwent curative‐intent resection of sarcoma lung metastases (2000–2016) were identified from the US Sarcoma Collaborative. Patients with extrapulmonary metastatic disease or R2 resections of primary tumor or metastases were excluded. Primary endpoint was OS. Results: Three hundred and fifty‐two patients met inclusion criteria. Location of primary tumor was truncal/extremity in 85% ( n = 270) and retroperitoneal in 15% ( n = 49). Forty‐nine percent ( n = 171) of patients had solitary and 51% ( n = 180) had multiple lung metastasis. Median OS was 49 months; 5‐year OS 42%. Age ≥55 (HR 1.77), retroperitoneal primary (HR 1.67), R1 resection of primary (HR 1.72), and multiple (≥2) lung metastases (HR 1.77) were associated with decreased OS(all p < 0.05). Assigning one point for each factor, we developed a risk score from 0 to 4. Patients were then divided into two risk groups: low (0–1 factor) and high (2–4 factors). The low‐risk group ( n = 159) had significantly better 5‐year OS compared to the high‐risk group ( n = 108) (51% vs. 16%, p < 0.001). Conclusion: We identified four characteristics that in aggregate portend a worse OS and created a novel prognostic risk score for patients with sarcoma lung metastases. Given that patients in the high‐risk group have a projected OS of <20% at 5 years, this risk score, after external validation, will be an important tool to aid in preoperative counseling and consideration for multimodal therapy.